2020
DOI: 10.1016/j.sjbs.2020.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Method for accurate diagnose of lupus erythematosus skin lesions based on microbial rDNA sequencing

Abstract: This study used microbial rDNA sequencing for accurate detection of systemic lupus erythematosus (SLE) skin lesions. 20 lupus erythematosus dermatology patients and 20 healthy persons were selected as experimental group and control group. Feces and serum of the subjects were sampled in sterile environment. Serum samples were examined for anti dsDNA antibodies. Fecal samples were analyzed by 16 s rDNA high-throughput sequencing, using Illumina MiSeq 2 × 250 sequencing platform. The results suggested that positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Sodium butyrate dampens the pro brotic response induced by TGF-β1 in human dermal broblasts [38]. A study reported higher abundance levels of genus Turicibacter in patients with systemic lupus erythematosus than in healthy individuals [39]. These results are consistent with those of our study and support the existence of a gut-skin axis.…”
Section: Discussionsupporting
confidence: 92%
“…Sodium butyrate dampens the pro brotic response induced by TGF-β1 in human dermal broblasts [38]. A study reported higher abundance levels of genus Turicibacter in patients with systemic lupus erythematosus than in healthy individuals [39]. These results are consistent with those of our study and support the existence of a gut-skin axis.…”
Section: Discussionsupporting
confidence: 92%
“…However, SLE patients in most cohorts both active and remissive, both adults and children all manifested the enrichment of Lactobacillus in both fecal and oral sample in China and Netherlands ( 14 , 15 , 18 , 19 , 46 ) ( Table 1 ). Notably, Lactobacillus enriched in active SLE patients and lupus erythematosus skin lesions patients ( 47 ) as disease severity might play a role in abundance ( 14 ). It is hard to illustrate whether the Lactobacillus correlated with disease severity or higher dose of GC treatment.…”
Section: Lactobacillus Are Altered In Sle Patientsmentioning
confidence: 99%
“…52 Several studies have shown that intestinal microorganisms play a key role in the maintenance of immune homeostasis. 53 This study demonstrated that the diversity and composition of the intestinal bacteria had significantly altered in rats with cyclophosphamide-induced immunosuppression but OP treatment reversed those changes. A significant increase in the proportion of Firmicutes and Bacteroidetes was also observed.…”
Section: Discussionmentioning
confidence: 75%